COMPARISON OF VISUAL ACUITY AFTER A COMBINATION OF CITICHOLINE AND METHYLPREDNISOLONE WITH A SINGLE CITICHOLINE TREATMENT IN NON-ARTERITIC ANTERIOR ISCHEMIC OPTIC NEUROPATHY PATIENTS: Oral Presentation - Observational Study - Resident - NADYA BEATRIX YOHANNA N.; Antonia Kartika; Ine Renata Musa; Rusti Hanindya Sari; Dianita Veulina Ginting; Prettyla Yollamanda (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Non-arteritic anterior ischemic optic neuropathy (NAION) accounts for 90-95% of optic neuropathy in the elderly with symptoms of decreased visual acuity. Posterior ciliary brevis hypoperfusion results in ischemia, triggers oxidative stress, axonal edema as well as compartment syndrome leading to retinal ganglion cell death via apoptosis. There is no gold standard therapy for NAION. Citicholine as a neuroprotector agent has shown satisfactory results in the acute and chronic phases. Methylprednisolone is also a therapeutic consideration that decreases capillary permeability thereby promoting faster resolution of disc edema. This study aimed to compare visual acuity in NAION patients with combination therapy of citicholine and methylprednisolone with single citicholine therapy. Methods : An analytical observational study with retrospective data collection at the National Eye Center of Cicendo Hospital for the period January 2021–February 2022. A total of 59 NAION patients who met the inclusion criteria were then divided into 2 groups, namely receiving a combination of citicholine with corticosteroids and single citicholine treatment. Results : The mean age in the combination group was 52.57±9.035 and the single group was 57.52±10.319. The number of men and women in the combination group were the same while in the single group women was higher. The risk factors obtained were hypertension, diabetes mellitus (DM), dyslipidemia, and smoking. There was a significant mean difference between initial visual acuity and3 months after therapy in the combination therapy group (p=0.0001) and in the single group. (p=0.002) Conclusion : Visual acuity in NAION patients with combination therapy of citicholine and methylprednisolone is better than citicholine alone.